9x+2-3=-3+9x

Simple and best practice solution for 9x+2-3=-3+9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+2-3=-3+9x equation:


Simplifying
9x + 2 + -3 = -3 + 9x

Reorder the terms:
2 + -3 + 9x = -3 + 9x

Combine like terms: 2 + -3 = -1
-1 + 9x = -3 + 9x

Add '-9x' to each side of the equation.
-1 + 9x + -9x = -3 + 9x + -9x

Combine like terms: 9x + -9x = 0
-1 + 0 = -3 + 9x + -9x
-1 = -3 + 9x + -9x

Combine like terms: 9x + -9x = 0
-1 = -3 + 0
-1 = -3

Solving
-1 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 40x+4-3y= | | g/7=-21 | | 2(x+5)=4x-7(x+3) | | 12x^3-2x^2-30x=0 | | 5(3-2x)=8-6(2-5x) | | 11x+233y= | | 8/x-7 | | 1.2=14.4 | | y=1000+5x | | 10b^2-3b-35=0 | | -5x-3y=-14 | | 3[1+4n]-2[5n-3]=25 | | -2p-4(6-2p)=4(p-2)-14 | | -5x+4y=7 | | 14x-14=7x-7 | | 3/2x2/4 | | 14x-7=7x-7 | | y=-4+-1 | | 1/3(5y-2)+1/12(6y+13) | | -3-4n= | | -5n=80 | | W^2+5wj-24j^2=0 | | 4x-7-9x=28 | | 3x+10-7x=70 | | -2x+8y=-6 | | -5y-5[-6-2y]=0 | | y-5.5=0 | | -33.072-(-41.03)= | | -2[-7k+4]+9=-13 | | 2x-88-117= | | -4(2n+3)+7(n+2)=15 | | 8x^2-10x+1=0 |

Equations solver categories